Bewertung des Eintrags von Pflanzenschutzmitteln in Oberflächengewässer. Runoff, Erosion und Drainage. GERDA - GEobased Runoff, erosion and Drainage risk Assessment for Germany. Abschlussbericht. - (:unkn) unknown (My University, 2017)
In dem in diesem Bericht dargestellten Projekt wurde das Konzept GERDA (GEobased Runoff, Erosion, and Drainage risk Assessment for Germany) entwickelt, mit dem zukünftig im Zulassungsverfahren von Pflanzenschutzmitteln (PSM) in Deutschland die Exposition von Oberflächengewässern durch Wirkstoff-Einträge über Runoff und Erosion, Drainage, Abdrift und atmosphärischen Transport bewertet werden kann. Zentrales Element in GERDA bildet die statistisch fundierte, Perzentil-basierte Auswahl der Boden-Klima-Szenarien, mit denen mittels der Modelle PRZM und MACRO die Expositionsabschätzung für einen Wirkstoff im Rahmen der Zulassungsprüfung durchgeführt wird. Der Bericht umfasst weiterhin die methodischen Grundlagen der Entwicklung von Boden-Klima-Szenarien spezifisch für Deutschland, eine Schwachstellenanalyse des FOCUS-Ansatzes zur Expositionsabschätzung sowie die Analyse des Modells VFSMOD als Option zur Risikominderung durch Filterstreifen im Zulassungsverfahren.

The assessment scheme GERDA (GEobased Runoff, Erosion, and Drainage risk Assessment for Germany) was developed to evaluate the exposure of surface waters from pesticide input via runoff, erosion, drainage, spray drift and atmospheric deposition for the authorization of plant protection products in Germany. Main feature is a statistically reliable percentile-based selection of soil-climate scenarios, used by the models PRZM and MACRO (as core elements of GERDA) for exposure assessment. The PEC (predicted environmental concentrations) calculated by GERDA for various substances ranges between 83th to 93th percentile related to the spatio-temporal statistical population of ca. 132,000 km² potentially treated agricultural area in Germany and the weather time series 1982-2011. The assessment scheme is implemented in the software tool GERDA v.1. A comparison of PEC calculation according to GERDA and the currently used exposure model EXPOSIT for 13 substances demonstrates that surface water exposure due to runoff is of relevance compared to drainage and spraydrift. Exposure assessment with GERDA leads to tighter risk management measures compared to the current exposure assessment scheme. Furthermore the report presents the methodology for soil-climate scenarios developed specificly for Germany, explains some deficiencies of the FOCUS exposure assessment approach, and analyses the capability of the model VFSMOD for the simulation of efficiency of vegetated filter strips (VFS) as a risk mitigation measure.
Keywords: Umweltschutz; Landwirtschaft; Gewässerschutz; Oberflächengewässer; Pflanzenschutzmittel; Wirkstoff; Zulassungsverfahren; Sensitivitätsanalyse